VaAPL1 Promotes Starch Synthesis to Constantly Contribute to Soluble Sugar Accumulation, Improving Low Temperature Tolerance in Arabidopsis and Tomato - Liang, Guoping; Li, Yanmei; Wang, Ping; Jiao, Shuzhen; Wang, Han; Mao, Juan; Chen, Baihong (Frontiers in Plant Science, 2022)
ADP-glucose pyrophosphorylase (AGPase) is a key rate-limiting enzyme involved in starch synthesis. APL1, an AGPase large subunit, plays an important role in the growth and development of grapes; however, its function in withstanding low temperature (LT) remains elusive. Hence, VaAPL1 was cloned from Vitis amurensis (Zuoshan I), and its function was characterized. The gene was highly expressed in the phloem of V. amurensis during winter dormancy (0, −5, and −10 °C). Phylogenetic relationships demonstrated that VaAPL1 was closely genetic related to SlAPL1 (from Solanum lycopersicum), and clustered into I group. Further, VaAPL1 was ectopically expressed in Arabidopsis thaliana (ecotype Columbia, Col) and tomato (“Micro-Tom” tomato) to characterize its function under LT. Compared with Col, the average survival rate of VaAPL1-overexpressing A. thaliana exceeded 75.47% after freezing treatment. Moreover, reactive oxygen species (ROS) content decreased in VaAPL1-overexpressing A. thaliana and tomato plants under LT stress. The activities of AGPase, and starch contents in VaAPL1-overexpressing A. thaliana were higher than in Col after LT stress. The contents of sucrose and glucose were accumulated in overexpressing plants compared with wild-type at 0 h and 24 h after LT stress. Transcriptome sequencing of overexpressing tomato plants revealed involvement in sugar metabolism and the hormone signal pathway, and Ca2+ signaling pathway related-genes were up-regulated. Hence, these results suggest that overexpression of VaAPL1 not only ensured sufficient starch converting into soluble sugars to maintain cell osmotic potential and provided energy, but also indirectly activated signal pathways involved in LT to enhance plant tolerance.